Model composition by reusing Petri net based modules - Costa, Aniko (2013)
In the last decades, embedded system controllers design is facing sustainable increasing complexity. This brings new challenges that can benefit from model based development approaches. Petri nets are one of the formalisms suitable to be used as system specification language. This paper proposes a method for model composition, starting from sub-models representing concurrent components, and relying on their composition using a bottom-up approach, while supporting the reusability of modules. This bottom-up approach is integrated with a previous top-down decomposition approach of the system model, using the net splitting operation, where sub-models associated with components are generated. In this sense, the proposed technique supports a balanced usage of top-down and bottom-up approaches to system modeling using model-based development of embedded system controllers where Petri nets play a central role.